الحوادث التى تقع يوم القيامة وتذكر في القرآن الكريم - Fransisca, Malia (At-Tuhfah : Jurnal Studi Keislaman, 2018)
Doomsday is divided into two: Sughro Doomsday and Kubro. Sughro doomsday like death, accidents, illness, etc. Kubro doomsday happen when the earth is shaken with fierce, all of the material the earth out, destroyed all of the universe. After that there is no life in the world. because life is actually going to happen in the hereafter. At the end of days coming, people running around like flying white ant. They are confused don’t know where they are going. The sky split. The ocean overflows. The mountains were destroyed all the way to dust. They are afraid of this terrible situation. They left and forget all valuable things, because at the time that can only help them is charity of their deeds, not possessions or property the other in the form of earthly.